#TITLE_ALTERNATIVE# - APRIANTO SUWONO (NIM: 15109027); Pembimbing: Dr. Ir. Samsul Bachri, M.Eng, EKO
Oil and gas exploration is the activities to find location which contains potential oil and gas reserves. These activities can be conducted either on land and ocean. Most common method which used for oil and gas exploration is marine seismic. In marine seismic, source and streamer geometry should be known accurately in order to get good result of seismic profiles. This information is used to determine the CMP (Common Mid Point) in seismic data processing and as position information on drilling positioning.In this research, navigation data are processed to determine source and streamer position. Source position is determined by calculating distance and bearing data from rGPS observation, while streamer position is defined through numerical reconstruction of streamer shape. The shape of streamer is reconstructed using combier method, which is divided into two steps: first step is reconstruct an approximate streamer shape with the compass measurements; then adjust the streamer position to fit the tailbuoy position. The tangent angle of each discretized segment of the streamer is estimated by interpolating the angle between compass measurements. This method has some limitations, which the magnetic declination data used for compass bird corrections are inaccurate and the presence of misfit tailbuoy after streamer rotation is still big in the y-axis. The results of source and streamer position will be verified with processed data from geometis MX software. From the comparison, the source and streamer model already resembles geometis MX results, because the difference between both results are not significant and has relatively similar pattern and shape.